Multispecialized proceedings in the case of a child with van der Waude syndrome - Siudzińska, Natalia (Interdyscyplinarne aspekty diagnozy i terapii logopedycznej, 2020)
The article presents the course of the treatment and improving the treatment of the four-year old boy born with van der Woude syndrome. The combination of the congenital defects that occur in this particular case of the syndrome are the complete cleft lip, alveolus and palate, salivary fistula on the bottom lip and considerable shortening of the tongue frenulum. Anatomical malformations in the child’s facial skeleton disturbed the development of the child’s speech, which in turn influenced his general development. Many years’ process of the boy’s treatment engages various specialists where each of them has played an important role. The crucial roles have been of a surgeon, an orthodontist, a phoniatrist, a laryngologist, a psychologist and a speech therapist. Coordinated cooperation of those specialists facilitates planning and implementing the adequate treatment and speech therapy forms. The progress the child has made proves that the treatment has been right and effective and that in this case the multi-specialist proceedings are necessary.